UAF1 is a subunit of multiple deubiquitinating enzyme complexes. - Cohn, M; Kee, Y; Haas, W; Gygi, S; D'Andrea, A (2009)
A balance between ubiquitination and deubiquitination regulates numerous cellular processes and pathways, and specific deubiquitinating enzymes often play the decisive role of controlling this balance. We recently reported that the USP1 deubiquitinating enzyme, which regulates the Fanconi anemia pathway by deubiquitinating the central player of the pathway, FANCD2, is activated by the WD40-repeat containing UAF1 protein through formation of a stable USP1/UAF1 protein complex. Here we present the isolation of two novel multisubunit deubiquitinating enzyme complexes containing USP12 and USP46, respectively. Both complexes contain the UAF1 protein as a bona fide subunit. Interestingly, UAF1 regulates the enzymatic activity of both enzyme complexes, suggesting that this activator protein may regulate a subclass of human deubiquitinating enzymes. We postulate that additional WD40-containing proteins may also form complexes with other human deubiquitinating enzymes and thereby regulate their activity and substrate specificity.